Cost-Effective Manufacturing of Microfluidics Through the Utilization of Direct Ink Writing - Prajitna, Stefanus H.; Harito, Christian; Yuliarto, Brian (Ital Publication, 2025)
Microfluidics is essential for precise manipulation of fluids in small channels. However, conventional manufacturing processes for microfluidic devices are expensive, time-consuming, and require specialized equipment in a clean room. While recent studies have improved the cost-effectiveness of this device, there is still a need for further advancement in cost efficiency. Therefore, this study aimed to develop a custom-built direct-ink writing (DIW) printer for manufacturing microfluidic devices that is more affordable. Custom-built DIW directly printed microfluidic channels onto microscope slide glass using RTV (Room Temperature Vulcanizing) silicone sealant. To finish the microfluidics manufacturing, the printed channel will be assembled by placing the same glass on top of the printed layer. This method eliminated the need for polydimethylsiloxane (PDMS) molds and casting processes that were still found in recent studies. This innovative 250 (USD) custom-built DIW method takes 15 seconds to print microfluidics channels and showed a significant cost reduction, with each microfluidics device costing only 0.071 (USD) compared to 0.90 (USD) in previous studies. This study makes microfluidics more affordable and accessible for biomedical use. Doi: 10.28991/ESJ-2025-09-01-01 Full Text: PDF